VD_FINDINFO Jug / 2015 / 222 vom 2. Juli 2015 - VD Tribunal cantonal (2015)
QUALITÉ POUR RECOURIR, RETRAITVOIE DE DROIT, PLAINTE PÉNALE, INDEMNITÉEN GÉNÉRAL | 33 CP, 382 al. 1 CPP (CH), 403 al. 1 let. a CPP (CH), 429 al. 1 let. a CPP (CH), 432 CPP (CH)